Cybersecurity Law Reform in Indonesia: National Sovereignty and Global Responsibility - Nono, Johanes De Brito Siga (Badan Pembinaan Hukum Nasional, 2025)
Global cybersecurity is currently facing increasingly complex challenges, with threats that are transnational in nature and rapidly evolving. In this context, Indonesia as a country with a rapidly growing digital economy must navigate the dilemma between maintaining national sovereignty actively participating in international cooperation. This article explores the challenges faced by Indonesia. By employing a normative juridical approach combined with qualitative analysis, this study examines the dynamics of cybersecurity law reform in Indonesia. Through descriptive analytical methods and the use of secondary legal materials, this article identifies existing gaps in the current legal framework and offers recommendations for more adaptive legal reforms. By integrating the principles of national sovereignty with global responsibility, the article proposes legal solutions that bridge the gap between domestic and international cybersecurity policies. The proposed legal reforms are expected to enhance Indonesia's cyber resilience